PERAN GURU BK DALAM MENGATASI PENYALAHGUNAAN MEDIA SOSIAL PADA SISWA DI KECAMATAN WALENRANG UTARA DAN LAMASI - Alam Nur (Jurnal Panrita, 2020)
Counseling Guidance (BK) in overcoming the negative influence of the development of information technology is very influential or decisive in order to prevent student moral decay, the efforts made at MTs Batusitanduk were a major breakthrough by prioritizing preventive efforts (prevention) not by repression. The activities carried out are by minimizing or even not providing opportunities for students to socialize freely. Restrict time and involve all related elements such as teachers and parents. The method BK teacher combine several approachesnamely; Behavioristic with behavior change techniques and electic approaches, namely a combination of directive and non-directive approaches. At the beginning of the program there were obstacles in the form of some parents not supporting the school program and even tending to support children's bad behavior. However, after going through good communication between the school and the parents, the two parties finally had an understanding. Keywords: Misuse of Social Media, The Role of Counseling Teachers